Research on greedy reconstruction algorithms of compressed sensing based on variable metric method - Pan-pan LIU; Lei LI; Hao-yu WNAG (Tongxin xuebao)
A variable metric method based gradient pursuit algorithm based on some existing gradient pursuit algorithms was proposed by combining the gradient direction of optimization methods with greedy algorithms.The computational complexity and storage requirements of these algorithms were also analysed and compared.In experimental part,all these algorithms were used to reconstruct one-dimensional audio signal and two-dimensional image signal.Experimental results show that the VMMGP algorithm has the best reconstruction performance among all the gradient pursuit algorithms.